The critical pressure of chromium - Pedrazzini, Pablo; Pedrazzini, P.; Jaccard, D. (Elsevier, 2008)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro, Argentina; University of Geneva; Suiza